Innovation of Flipbook Teaching Materials in Supporting Student Learning Independence - Rahmadani, Ervi; Bungawati, Bungawati (Mimbar Sekolah Dasar, 2024)
Currently, it is still rare to find teaching materials that are innovative and use technology, so they have an impact on decreasing student motivation and independence in learning. The purpose of this study was to describe the stages of developing teaching materials, determine the validity and practicality of the teaching materials produced and determine the level of independence of students after using these teaching materials. This type of research is research and development by adapting the 4D development model. The steps are Define, Design, Develop, and Disseminate. The subjects in this study were 16 fifth grade students and teachers at SD Negeri 173 Gaya Baru, Tellu Limpoe District, Bone Regency. The instruments used in this study were interview guidelines, validation sheets, student and teacher response questionnaires and learning independence questionnaires. The results showed that the resulting product was in the form of Flipbook teaching materials with the help of the Publuu application which was developed containing material in the form of reading materials, pictures, videos and evaluation through 3 stages of define, design and development. The data from the material expert validation results is 96.9% in the valid category and the media expert validation results are 76.6% which are in the valid category. In addition, the practicality test shows that the average student response is 89% and the teacher's response is 90.26% which is in a very high practicality category, so that it influences student learning independence. This flipbook-shaped teaching material makes a contribution to elementary schools for use in the learning process, because it is practical and flexible.